Futebol, criança e valores políticos - Sousa, Alberto Monteiro Barroso de (2012)
Soccer in Brazil is a mass and elite Sport that crosses social classes and brings everyone together in one sole objective: the goal. Usually soccer is seem as leisure, beyond entertainment, and what are the values transmitted or reinforced by soccer? The present study has as its objective to research the relation between values transmitted through soccer with values in children between the ages of 10 to 12 years old. In observing a soccer game one finds that errors and subsequent injustices happen with frequency even though not always is the injustice committed perceived as being something bad, for at the same time it is seem a good by the team and supporters favored and bad for the team and supporters disadvantaged since that sentiment of justice and injustice frequently occurs during a soccer match generating the banalization of injustice since not always injustice is felt as something negative. This is an exploratory study, studying political values that are transmitted by means of soccer to children in their phase of political socialization and the study presents a new method for studying values in children. The main focus of the theoretical framework is based on the supposition that modalities of political conscienciousness and forms of individual and collective actions vary according with everyday life routines with restrictions found in everyday life and with cultural notions of values and beliefs in social relations. The findings of the study show that for adversaries the rules ought to apply more rigidly than for allies and a close personal affinity with some soccer player had a strong influence on the understanding of justice by the children under study